1984
DOI: 10.1083/jcb.98.6.2047
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural localization of the mannose 6-phosphate receptor in rat liver.

Abstract: An affinity-purified rabbit antibody against rat liver mannose 6-phosphate receptor (MP-R) was prepared. The antibody was directed against a 215 kd-polypeptide and it recognized both ligand-occupied and free receptor . Anti-MP-R was used for immunofluorescence and immunoelectron microscopy of cryosections from rat liver. MP-R was demonstrated in all parenchymal liver cells, but not in endothelial lining cells. MP-R labeling was found at the entire plasma membrane, in coated pits and coated vesicles, in the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
66
2

Year Published

1985
1985
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(78 citation statements)
references
References 39 publications
(52 reference statements)
10
66
2
Order By: Relevance
“…2a). These albumin-positive vesicles were distinct from LAMP carriers by their irregular shape, dense content and lack of internal membranes 23 (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…2a). These albumin-positive vesicles were distinct from LAMP carriers by their irregular shape, dense content and lack of internal membranes 23 (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…proximally to the coated compartment, it is expected to take place in the Golgi stack. For lysosomal enzymes, the proper sorting of these proteins depends on the presence of mannose-6-phosphate residues which are recognized by corresponding receptors on the sorting compartment [15]; such receptors for mannose-6-phosphate have recently been demonstrated on the cisternae of the Golgi complex and this has been taken to imply that sorting of lysosomal enzymes can occur at this level [16,17].…”
Section: (Pro)insulin Biosynthesis Sorting and Conversionmentioning
confidence: 99%
“…This concept was developed largely from immunogold labeling experiments using VSV-G and other viral spike proteins as well as several endogenous transmembrane proteins. These studies showed that all cisternae, including the trans-most, appear to be labeled (see for example, Geuze et al, 1984;Orci et al, 1987). However, individual thin sections rarely reveal the full extent of the cisternae in a given Golgi stack, because of convolution of the membranes and the presence of openings in the cisternae, such as fenestrae and "holes" (Rambourg et al, 1979;Rambourg and Clermont, 1990;Ladinsky et al, 1999).…”
Section: Introductionmentioning
confidence: 99%